THE IMPORTANCE OF STRENGTHENING LEGAL PROFESSIONAL ETHICS EDUCATION IN INDONESIA TOWARDS ERA 6.0 - Putra, Restu Adi; Windradi, Fitri; Mafazi, Agung (Proceeding of International Conference on Multidisciplinary Research, 2024)
The creation of justice and legal certainty in society cannot be separated from law enforcement agencies as a milestone in upholding the rule of law. The role of law enforcers is important as a driving force for law enforcement agencies to run following their duties, principles and function. The importance of the role of law enforcers makes law colleges or law faculties as a creator of competent and professional law enforcement personnel candidates very necessary to pay serious attention to their education system, especially about professional ethics. Entering era 6.0 with all the ease of technology and information, professional ethics-based education must be improved so that the aspects of convenience provided do not eliminate ethical and moral values. The type of research used in this paper is normative juridical. The conclusion of this paper is the need to strengthen legal professional ethics education towards era 6.0 by using two models of approaches, namely non-curricular approaches and curricular approaches.